Status of the Pied Imperial Pigeon Ducula bicolour and Pink-necked Green-Pigeon Treron vernans on Flores, Nusa Tenggara - Schellekens, Mark; Trainor, Colin R; Encallado, Juan Jose Ramos; Imansyah, M Jeri (KUKILA, 2009)
The status of the Pied Imperial Pigeon Ducula bicolor in Nusa Tenggara (Lesser Sundas) is unclear, whilst the Pink-necked Green-Pigeon Treron vernans is unknown east of Sumbawa. We document observations of these two species on Flores and surrounding islands, and conclude that the Pied Imperial Pigeon is probably resident in western Flores and the Komodo area, whereas the Pink-necked Green-Pigeon has probably colonised Flores within the last 5-l 0 years. Green-Pigeons in the region should be carefully examined in the future.